Incorporating the Detection of Single Nucleotide Polymorphisms Associated With Invasive Aspergillosis Into the Clinic - White, P. Lewis; Price, Jessica S. (Frontiers in Cellular and Infection Microbiology, 2022)
Exposure to fungi is inevitable, yet only a small number of patients with significant clinical risk develop invasive aspergillosis (IA). While timing of exposure in relation to immune status, environmental and occupational factors will influence the probability of developing IA, factors specific to the individual will likely play a role and variation in the host’s genetic code associated with the immunological response to fungi have been linked to increased risk of developing IA. Screening for SNPs in genes significantly associated with IA (e.g. Pentraxin-3, Toll-like receptor 4, Dectin-1, DC-SIGN) could form part of the clinical work-up on admission or post allogeneic stem cell transplantation, to complement fungal biomarker screening. Through the combination of clinical and genetic risk with mycological evidence, we are approaching a time when we should be able to accurately predict the risk of IA in the haematology patient, using predictive modelling to stratifying each individual’s management. Understanding the host and their immune responses to infection through genomics, transcriptomics and metabolomics/proteomics is critical to achieving how we manage the individual’s risk of IA, underpinning personalized medicine. This review will investigate what is known about the genetic risk associated with developing IA, primarily in haematology patients and whether these strategies are ready to be incorporated into routine clinical practice, and if not what are the remaining hurdles to implementation.